Manufacturing method of lightweight and high-strength magnesium alloy brake disc

By optimizing the composition and manufacturing process of magnesium alloy, combined with refining agent and microarc oxidation technology, the problem of degradation of magnesium alloy brake discs at high temperatures is solved, high strength and wear resistance are achieved, and the service life and safety of the brake discs are improved.

CN120210579BActive Publication Date: 2025-08-12烟台美丰机械集团有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510653959.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-12
Estimated Expiration
2045-05-21

AI Technical Summary

Technical Problem

The existing magnesium alloy brake discs have reduced mechanical properties in high temperature environments, and their wear resistance and corrosion resistance are insufficient, which affects the service life and safety of the brake discs.

Method used

The magnesium alloy melt formula of specific components is used, combined with thiol-titanium coordination refining agent, Al-5Ti-1B intermediate alloy deterioration treatment, low-pressure casting and microarc oxidation technology, to form a dense ceramic film to improve the strength and wear resistance of the magnesium alloy brake disc.

Benefits of technology

It significantly improves the strength and wear resistance of magnesium alloy brake discs, extends service life, reduces corrosion risks, and meets the requirements of the use of automobile brake systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a lightweight, high-strength magnesium alloy brake disc, and belongs to the technical field of brake disc manufacturing. Magnesium is placed in a furnace to melt it, and then aluminum, zinc, manganese, rare earth elements, and silicon are added in sequence, stirred and mixed to form a uniform magnesium alloy melt; a mercapto-titanium coordination type refining agent is added to the magnesium alloy melt for refining treatment; after the melt is cooled, an Al-5Ti-1B intermediate alloy is added for modification treatment; the refined and modified magnesium alloy melt is poured into a preheated mold, and the cast-molded magnesium alloy brake disc is subjected to solid solution treatment and aging treatment; the heat-treated magnesium alloy brake disc is surface-treated, and a dense ceramic film is formed on the surface of the brake disc using micro-arc oxidation technology; the magnesium alloy brake disc prepared by the present invention has good mechanical properties and wear resistance, and can meet the use requirements of automobile braking systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of brake disc manufacturing, in particular to a method for manufacturing a lightweight and high-strength magnesium alloy brake disc. Background Art

[0002] With the rapid development of the automotive industry, lightweight vehicle design has become an important means of improving fuel economy and reducing emissions. As a key component of the automotive braking system, the performance of brake discs directly impacts braking safety and the driving experience. Traditional brake discs are mostly made of cast iron. While this material offers excellent wear resistance and thermal stability, it is heavy and hinders the development of lightweight vehicles.

[0003] Magnesium alloys offer advantages such as low density, high specific strength, and excellent shock absorption, making them ideal lightweight materials. However, the application of magnesium alloys in brake disc manufacturing currently faces numerous challenges. For example, magnesium alloys have poor high-temperature strength and wear resistance. During braking, the brake disc generates a large amount of heat, which significantly reduces the mechanical properties of the magnesium alloy in high-temperature environments, shortening the brake disc's service life and increasing unstable braking performance. Furthermore, the corrosion resistance of magnesium alloys needs to be improved, as they are prone to corrosion in humid and corrosive environments, impacting the safety of the brake disc. Therefore, the development of a magnesium alloy brake disc that is both lightweight and high-strength, and a method for its manufacture, is of great practical significance. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides a method for manufacturing a lightweight and high-strength magnesium alloy brake disc, the operating steps of which are as follows:

[0005] S1: Preparation of magnesium alloy melt: Prepare raw materials of 6-8% aluminum, 2-3% zinc, 0.3-0.5% manganese, 0.5-1% rare earth elements, 0.2-0.4% silicon, and the balance magnesium; Place magnesium in a furnace, heat to 650-700°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0006] S2 refining treatment: adding 0.3-0.5% of the mass of the melt of the magnesium alloy to a mercapto-titanium coordination type refining agent for refining treatment to remove gas and impurities in the magnesium alloy melt and improve the quality of the magnesium alloy;

[0007] S3 modification treatment: Lower the temperature of the magnesium alloy melt to 620-650°C, add 0.2-0.3% of the melt mass of Al-5Ti-1B master alloy to the melt for modification treatment, stir evenly and let it stand for 10-15 minutes; modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties;

[0008] S4 mold preheating: Preheat the mold used to manufacture brake discs to 200-250℃ to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the filling and the quality of the casting;

[0009] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2-3m / s and the casting temperature is 630-660℃;

[0010] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0011] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0012] As a preferred embodiment of the present invention, the rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0013] As a preferred embodiment of the present invention, the refining treatment temperature is 680-720° C., and the refining time is 15-20 minutes.

[0014] As a preferred embodiment of the present invention, during the casting process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02-0.05 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the occurrence of defects such as pores and shrinkage.

[0015] As a preferred embodiment of the present invention, the solution treatment temperature is 410-430° C., the holding time is 4-6 hours, and then the solution is rapidly cooled to room temperature.

[0016] As a preferred embodiment of the present invention, the aging treatment temperature is 170-190° C., the holding time is 8-10 hours, and then the product is air-cooled to room temperature.

[0017] As a preferred embodiment of the present invention, the voltage of the micro-arc oxidation is 300-400V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20-30 minutes; the mass concentration of sodium silicate in the electrolyte is 10-20g / L, and the mass concentration of sodium hydroxide is 5-15g / L.

[0018] As a preferred embodiment of the present invention, the preparation method of the mercapto-titanium coordination type refining agent is as follows:

[0019] T1: Add 40-50 parts of magnesium thioglycolate, 1000-1500 parts of anhydrous ethanol, and 15-20 parts of titanium oxysulfate into a reactor, stir at 50-60°C for 2-5 hours, and use TiO2 + The coordination reaction with -SH generates an intermediate;

[0020] T2: Add 1-4 parts of spherical polymethylsilsesquioxane resin and 150-200 parts of nano-boron nitride, and disperse them by ultrasonication for 1-3 hours; remove ethanol by vacuum distillation under reduced pressure, and vacuum dry at 80-100°C for 4-6 hours. Crush the mixture through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

[0021] Reaction mechanism: Molecular design innovation: Through the dual effects of Ti-OS coordination bond and Si-O-Ti covalent bond, "active ingredient stabilization + functional group efficiency" is achieved.

[0022] Structural synergistic effect: The combination of silsesquioxane three-dimensional network and nano-BN solves the problems of rapid high-temperature decomposition and poor dispersibility of traditional refining agents.

[0023] Multi-mechanism coupling: Integrates the three major functions of "impurity adsorption, grain refinement, and gas removal" into a single refining agent, breaking through the single function limitations of traditional methods.

[0024] Synergistic mechanism of the refining process: triple effect of “adsorption-nucleation-degassing”.

[0025] Impurity adsorption: sulfhydryl radicals (·SH) and K in the melt + 、Na + The alkali metal ions form stable thiolates, reducing their activity; the titanium-sulfur complex wraps the MgO particles through coordination bonds, causing them to precipitate from the melt.

[0026] Grain refinement: TiO2 nanocrystals generated by the decomposition of titanium oxide intermediates and nano-boron nitride act together as heterogeneous nucleation cores, which increases the nucleation rate and refines the grain size.

[0027] Gas removal: The methyl radicals (·CH3) produced by the decomposition of silsesquioxane react with hydrogen (H2) in the melt to produce methane (CH4), which promotes gas escape.

[0028] Compared with the prior art, the method for manufacturing a lightweight, high-strength magnesium alloy brake disc of the present invention has the following beneficial effects:

[0029] 1. Breakthrough in impurity removal efficiency: The content of inclusions such as MgO and Al2O3 is reduced, reducing internal defects in castings; the residual amount of K and Na is reduced, avoiding corrosion cracking caused by grain boundary segregation.

[0030] 2. Significantly improved mechanical properties: By optimizing the composition of magnesium alloy, adding alloying elements such as aluminum, zinc, manganese, rare earth elements and silicon, and adopting special manufacturing processes, including refining, modification and heat treatment, the grain size of magnesium alloy is refined and the strength of the alloy is improved.

[0031] 3. Excellent wear resistance and corrosion resistance: The ceramic film formed on the surface of the brake disc by micro-arc oxidation treatment has the advantages of good wear resistance and strong chemical stability. It can effectively improve the wear resistance and corrosion resistance of the brake disc and extend the service life of the brake disc. DETAILED DESCRIPTION

[0032] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description in combination with embodiments and comparative examples.

[0033] Example 1: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, comprising the following steps:

[0034] S1: Preparation of magnesium alloy melt: Prepare raw materials of 6% aluminum, 2% zinc, 0.3% manganese, 0.5% rare earth elements, 0.2% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 650°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0035] S2 refining treatment: adding 0.3% of the mass of the melt to the magnesium alloy melt, a mercapto-titanium coordination type refining agent, to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0036] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 620°C, and 0.2% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 10 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0037] S4 mold preheating: Preheat the mold used to manufacture brake discs to 200°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0038] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2m / s and the casting temperature is 630℃;

[0039] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0040] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0041] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0042] The refining temperature is 680° C. and the refining time is 15 minutes.

[0043] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0044] The solution treatment temperature is 410° C., the holding time is 4 hours, and then the steel is rapidly cooled to room temperature.

[0045] The aging treatment temperature is 170° C., the holding time is 8 hours, and then the steel is air-cooled to room temperature.

[0046] The voltage of the micro-arc oxidation treatment is 300V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20 minutes; the mass concentration of sodium silicate in the electrolyte is 10g / L, and the mass concentration of sodium hydroxide is 5g / L.

[0047] The preparation method of the mercapto-titanium coordination type refining agent is as follows:

[0048] T1: 40g magnesium thioglycolate, 1000g anhydrous ethanol, and 15g titanyl sulfate were added to a reactor and stirred at 50°C for 2 hours. + The coordination reaction with -SH generates an intermediate;

[0049] T2: 1 g of spherical polymethylsilsesquioxane resin and 150 g of nano-boron nitride were added, and ultrasonic dispersion was performed for 1 hour. After removing ethanol by vacuum distillation under reduced pressure, the mixture was vacuum dried at 80°C for 4 hours and crushed through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

[0050] Example 2: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, comprising the following steps:

[0051] S1: Preparation of magnesium alloy melt: Prepare raw materials of 7% aluminum, 2.5% zinc, 0.4% manganese, 0.6% rare earth elements, 0.3% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 660°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0052] S2 refining treatment: adding 0.4% of the mass of the melt to the magnesium alloy melt, a mercapto-titanium coordination type refining agent, to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0053] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 630°C, and 0.2% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 12 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0054] S4 mold preheating: Preheat the mold used to manufacture brake discs to 210°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0055] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2 m / s and the casting temperature is 640°C;

[0056] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0057] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0058] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0059] The refining temperature is 690° C. and the refining time is 16 minutes.

[0060] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.03 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0061] The solution treatment temperature is 420° C., the holding time is 5 hours, and then the steel is rapidly cooled to room temperature.

[0062] The aging treatment temperature is 180° C., the holding time is 9 hours, and then the steel is air-cooled to room temperature.

[0063] The voltage of the micro-arc oxidation treatment is 350V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 25 minutes; the mass concentration of sodium silicate in the electrolyte is 15g / L, and the mass concentration of sodium hydroxide is 10g / L.

[0064] The preparation method of the mercapto-titanium coordination type refining agent is as follows:

[0065] T1: 43g of magnesium thioglycolate, 1200g of anhydrous ethanol and 16g of titanyl sulfate were added to the reactor and stirred at 55°C for 3 hours. + The coordination reaction with -SH generates an intermediate;

[0066] T2: 2 g of spherical polymethylsilsesquioxane resin and 160 g of nano-boron nitride were added, and ultrasonic dispersion was performed for 2 hours. After removing ethanol by vacuum distillation under reduced pressure, the mixture was vacuum dried at 90°C for 5 hours and crushed through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

[0067] Example 3: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, the operating steps of which are as follows:

[0068] S1: Preparation of magnesium alloy melt: Prepare raw materials of 7% aluminum, 2.5% zinc, 0.4% manganese, 0.8% rare earth elements, 0.3% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 680°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0069] S2 refining treatment: adding 0.4% of the mass of the melt to the magnesium alloy melt, a mercapto-titanium coordination type refining agent, to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0070] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 640°C, and an Al-5Ti-1B master alloy accounting for 0.3% of the melt mass is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 14 minutes. The modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0071] S4 mold preheating: Preheat the mold used to manufacture brake discs to 240°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0072] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 3m / s and the casting temperature is 650℃;

[0073] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0074] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0075] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0076] The refining temperature is 710° C. and the refining time is 18 minutes.

[0077] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.04 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0078] The solution treatment temperature is 420° C., the holding time is 5 hours, and then the steel is rapidly cooled to room temperature.

[0079] The aging treatment temperature is 180° C., the holding time is 9 hours, and then the steel is air-cooled to room temperature.

[0080] The voltage of the micro-arc oxidation treatment is 350V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 25 minutes; the mass concentration of sodium silicate in the electrolyte is 15g / L, and the mass concentration of sodium hydroxide is 10g / L.

[0081] The preparation method of the mercapto-titanium coordination type refining agent is as follows:

[0082] T1: 48g of magnesium thioglycolate, 1400g of anhydrous ethanol and 18g of titanyl sulfate were added to a reactor and stirred at 55°C for 4 hours. + The coordination reaction with -SH generates an intermediate;

[0083] T2: 3 g of spherical polymethylsilsesquioxane resin and 180 g of nano-boron nitride were added and ultrasonically dispersed for 2 hours. After removing ethanol by vacuum distillation under reduced pressure, the mixture was vacuum dried at 90°C for 5 hours and crushed through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

[0084] Example 4: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, comprising the following steps:

[0085] S1: Preparation of magnesium alloy melt: Prepare raw materials of 8% aluminum, 3% zinc, 0.5% manganese, 1% rare earth elements, 0.4% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 700°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0086] S2 refining treatment: adding 0.5% of the mass of the melt to the magnesium alloy melt, a mercapto-titanium coordination type refining agent, to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0087] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 650°C, and 0.3% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 15 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0088] S4 mold preheating: Preheat the mold used to manufacture brake discs to 250°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0089] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 3m / s and the casting temperature is 660℃;

[0090] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0091] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0092] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0093] The refining temperature is 720° C. and the refining time is 20 minutes.

[0094] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.05 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0095] The solution treatment temperature is 430° C., the holding time is 6 hours, and then the steel is rapidly cooled to room temperature.

[0096] The aging treatment temperature is 190° C., the holding time is 10 hours, and then the steel is air-cooled to room temperature.

[0097] The voltage of the micro-arc oxidation treatment is 400V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 30 minutes; the mass concentration of sodium silicate in the electrolyte is 20g / L, and the mass concentration of sodium hydroxide is 15g / L.

[0098] The preparation method of the mercapto-titanium coordination type refining agent is as follows:

[0099] T1: 50g of magnesium thioglycolate, 1500g of anhydrous ethanol and 20g of titanyl sulfate were added to the reactor and stirred at 60℃ for 5 hours.+ The coordination reaction with -SH generates an intermediate;

[0100] T2: 4 g of spherical polymethylsilsesquioxane resin and 200 g of nano-boron nitride were added, and ultrasonic dispersion was performed for 3 hours. After removing ethanol by vacuum distillation under reduced pressure, the mixture was vacuum dried at 100° C. for 6 hours and crushed through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

[0101] Comparative Example 1: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, wherein the steps are as follows:

[0102] S1: Preparation of magnesium alloy melt: Prepare raw materials of 6% aluminum, 2% zinc, 0.3% manganese, 0.5% rare earth elements, 0.2% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 650°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0103] S2 refining treatment: adding hexachloroethane (0.3% by mass) to the magnesium alloy melt for refining treatment to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0104] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 620°C, and 0.2% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 10 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0105] S4 mold preheating: Preheat the mold used to manufacture brake discs to 200°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0106] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2m / s and the casting temperature is 630℃;

[0107] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0108] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0109] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0110] The refining temperature is 680° C. and the refining time is 15 minutes.

[0111] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0112] The solution treatment temperature is 410° C., the holding time is 4 hours, and then the steel is rapidly cooled to room temperature.

[0113] The aging treatment temperature is 170° C., the holding time is 8 hours, and then the steel is air-cooled to room temperature.

[0114] The voltage of the micro-arc oxidation treatment is 300V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20 minutes; the mass concentration of sodium silicate in the electrolyte is 10g / L, and the mass concentration of sodium hydroxide is 5g / L.

[0115] Comparative Example 2: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, wherein the steps are as follows:

[0116] S1: Preparation of magnesium alloy melt: Prepare raw materials of 6% aluminum, 2% zinc, 0.3% manganese, 0.5% rare earth elements, 0.2% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 650°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0117] S2 refining treatment: adding a refining agent accounting for 0.3% of the melt mass to the magnesium alloy melt for refining treatment to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0118] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 620°C, and 0.2% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 10 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0119] S4 mold preheating: Preheat the mold used to manufacture brake discs to 200°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0120] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2m / s and the casting temperature is 630℃;

[0121] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0122] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0123] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0124] The refining temperature is 680° C. and the refining time is 15 minutes.

[0125] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0126] The solution treatment temperature is 410° C., the holding time is 4 hours, and then the steel is rapidly cooled to room temperature.

[0127] The aging treatment temperature is 170° C., the holding time is 8 hours, and then the steel is air-cooled to room temperature.

[0128] The voltage of the micro-arc oxidation treatment is 300V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20 minutes; the mass concentration of sodium silicate in the electrolyte is 10g / L, and the mass concentration of sodium hydroxide is 5g / L.

[0129] The preparation method of the refining agent is:

[0130] T1: 40g magnesium thioglycolate, 1000g anhydrous ethanol, and 15g titanyl sulfate were added to a reactor and stirred at 50°C for 2 hours. + The coordination reaction with -SH generates an intermediate;

[0131] T2: Add 150 g of nano-boron nitride and disperse it ultrasonically for 1 hour; remove ethanol by vacuum distillation under reduced pressure, dry in a vacuum at 80°C for 4 hours, and crush through a 100-mesh sieve to obtain a refining agent.

[0132] Comparative Example 3: A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, wherein the steps are as follows:

[0133] S1: Preparation of magnesium alloy melt: Prepare raw materials of 6% aluminum, 2% zinc, 0.3% manganese, 0.5% rare earth elements, 0.2% silicon, and the balance magnesium; Place magnesium in a furnace and heat to 650°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt;

[0134] S2 refining treatment: adding a refining agent accounting for 0.3% of the melt mass to the magnesium alloy melt for refining treatment to remove gas and impurities in the melt and improve the quality of the magnesium alloy;

[0135] S3 modification treatment: The temperature of the magnesium alloy melt is lowered to 620°C, and 0.2% of the melt mass of Al-5Ti-1B master alloy is added to the melt for modification treatment. After stirring evenly, the melt is allowed to stand for 10 minutes. Modification treatment can refine the grain size of the magnesium alloy and improve its mechanical properties.

[0136] S4 mold preheating: Preheat the mold used to manufacture brake discs to 200°C to reduce heat loss of the magnesium alloy melt during the pouring process, ensuring the integrity of the mold filling and the quality of the casting;

[0137] S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2m / s and the casting temperature is 630℃;

[0138] S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; heat treatment can further improve the strength and hardness of the magnesium alloy brake disc;

[0139] S7 surface treatment: The heat-treated magnesium alloy brake disc is surface treated and micro-arc oxidation technology is used to form a dense ceramic film on the surface of the brake disc. The ceramic film can significantly improve the wear resistance and corrosion resistance of the brake disc.

[0140] The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:1.

[0141] The refining temperature is 680° C. and the refining time is 15 minutes.

[0142] During the pouring process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02 MPa, so that the magnesium alloy melt can better fill the mold cavity and reduce the generation of defects such as pores and shrinkage.

[0143] The solution treatment temperature is 410° C., the holding time is 4 hours, and then the steel is rapidly cooled to room temperature.

[0144] The aging treatment temperature is 170° C., the holding time is 8 hours, and then the steel is air-cooled to room temperature.

[0145] The voltage of the micro-arc oxidation treatment is 300V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20 minutes; the mass concentration of sodium silicate in the electrolyte is 10g / L, and the mass concentration of sodium hydroxide is 5g / L.

[0146] The preparation method of the refining agent is:

[0147] T1: 40g magnesium thioglycolate, 1000g anhydrous ethanol, and 15g titanyl sulfate were added to a reactor and stirred at 50°C for 2 hours. + The coordination reaction with -SH generates an intermediate;

[0148] T2: 1 g of spherical polymethylsilsesquioxane resin was added and ultrasonically dispersed for 1 hour. After removing ethanol by distillation under reduced pressure, the mixture was vacuum dried at 80°C for 4 hours and crushed through a 100-mesh sieve to obtain a refining agent.

[0149] 1. Tensile strength test: Tested on SSS-1120 electronic universal testing machine in accordance with GB228.

[0150] 2. Linear wear rate test: The test is carried out using MM-1000 friction and wear testing machine.

[0151] The test results obtained by the above test method are shown in Table 1 below.

[0152] Table 1: Test results of various embodiments and comparative examples

[0153]

[0154] Through the data analysis of the above embodiments and comparative examples, the magnesium alloy brake disc prepared in the present invention has good mechanical properties and wear resistance, and can meet the use requirements of automobile braking systems.

[0155] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the scope of the technical solution of the present invention, make some changes or modifications to equivalent embodiments using the technical contents disclosed above. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for manufacturing a lightweight, high-strength magnesium alloy brake disc, characterized by: The steps are: S1: Preparation of magnesium alloy melt: Prepare raw materials of 6-8% aluminum, 2-3% zinc, 0.3-0.5% manganese, 0.5-1% rare earth elements, 0.2-0.4% silicon, and the balance magnesium; Place magnesium in a furnace, heat to 650-700°C to melt it, then add aluminum, zinc, manganese, rare earth elements, and silicon in sequence, stirring while adding to ensure that all elements are fully mixed to form a uniform magnesium alloy melt; S2 refining treatment: adding 0.3-0.5% of the mass of the melt of the mercapto-titanium coordination type refining agent to the magnesium alloy melt for refining treatment; S3 modification treatment: reduce the temperature of the magnesium alloy melt to 620-650℃, add 0.2-0.3% of Al-5Ti-1B master alloy to the melt for modification, stir evenly and let it stand for 10-15 minutes; S4 mold preheating: preheat the mold used to manufacture the brake disc to 200-250℃; S5 casting: The refined and modified magnesium alloy melt is poured into the preheated mold at a casting speed of 2-3m / s and the casting temperature is 630-660℃; S6 heat treatment: The cast magnesium alloy brake disc is subjected to solution treatment and aging treatment; S7 surface treatment: Surface treatment of heat-treated magnesium alloy brake discs, using micro-arc oxidation technology to form a dense ceramic film on the surface of the brake disc; The mercapto-titanium coordination refining agent is obtained by reacting magnesium thioglycolate, titanyl sulfate, spherical polymethylsilsesquioxane resin and nano boron nitride; The preparation method of the mercapto-titanium coordination type refining agent is as follows: T1: Add 40-50 parts of magnesium thioglycolate, 1000-1500 parts of anhydrous ethanol, and 15-20 parts of titanium oxysulfate into a reactor, stir at 50-60°C for 2-5 hours, and use TiO2 + The coordination reaction with -SH generates an intermediate; T2: Add 1-4 parts of spherical polymethylsilsesquioxane resin and 150-200 parts of nano-boron nitride, and disperse them by ultrasonication for 1-3 hours; remove ethanol by vacuum distillation under reduced pressure, and vacuum dry at 80-100°C for 4-6 hours. Crush the mixture through a 100-mesh sieve to obtain a mercapto-titanium coordination refining agent.

2. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, characterized in that: The rare earth element is a mixture of yttrium, lanthanum and cerium, and the mass ratio thereof is 1:1:

1.

3. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, characterized in that: The refining temperature is 680-720° C., and the refining time is 15-20 minutes.

4. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, wherein: During the casting process, low-pressure casting is adopted to maintain the pressure in the mold at 0.02-0.05 MPa.

5. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, characterized in that: The solution treatment temperature is 410-430° C., the holding time is 4-6 hours, and then the steel is rapidly cooled to room temperature.

6. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, characterized in that: The aging treatment temperature is 170-190° C., the holding time is 8-10 hours, and then the steel is air-cooled to room temperature.

7. The method for manufacturing a lightweight, high-strength magnesium alloy brake disc according to claim 1, characterized in that: The voltage of the micro-arc oxidation is 300-400V, the electrolyte is a mixed solution of sodium silicate and sodium hydroxide, and the treatment time is 20-30 minutes; the mass concentration of sodium silicate in the electrolyte is 10-20g / L, and the mass concentration of sodium hydroxide is 5-15g / L.

Citation Information

Patent Citations

  • Aluminum alloy micro-arc oxidization process

    CN107557840A

  • Extrusion casting process for making automobile engine rack of magnesium alloy

    CN1887480A